2020
DOI: 10.1021/acs.jchemed.0c00705
|View full text |Cite
|
Sign up to set email alerts
|

Learning Loss, a Potential Challenge for Transition to Undergraduate Study Following COVID19 School Disruption

Abstract: In a normal year approximately 3 months pass between students taking their final examinations in high school or college and beginning an undergraduate course in chemistry. In the months prior to those examinations, students will usually have undertaken an extensive period of revision and consolidation of the key concepts learned throughout their course. Some of this will be supported by their teachers and some will be independent study. The COVID19 pandemic resulted in the cancellation of these examinations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
1
35
2
3
Order By: Relevance
“…This suggests that the examination process is not involved in the acquisition of new knowledge. Contrary to expectations (Turner et al 2020), therefore, bioscience students did not enter university this academic year (2020/21) knowing or understanding less than in previous years. Examinations are sometimes seen as a motivation for learning (Koballa and Glyn 2007) but, rather than fostering understanding, they often involve cramming many, often disjunct, items of information into short-term memory for immediate retrieval.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…This suggests that the examination process is not involved in the acquisition of new knowledge. Contrary to expectations (Turner et al 2020), therefore, bioscience students did not enter university this academic year (2020/21) knowing or understanding less than in previous years. Examinations are sometimes seen as a motivation for learning (Koballa and Glyn 2007) but, rather than fostering understanding, they often involve cramming many, often disjunct, items of information into short-term memory for immediate retrieval.…”
Section: Discussioncontrasting
confidence: 76%
“…With the end-of-school grading process in doubt for 2021, focus needs to turn to student learning, as this is the best preparation for higher education, not the grading process. Tests will need to continue in future years to avoid misconceptions and potentially damaging assumptions (Turner et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the physical constraints and low motivation experienced by the students during the distance education process may have influenced this result. There are also studies which concluded that distance education caused a decrease in students' motivation (Niemi & Kousa, 2020;Turner, Hughes & Presland, 2020). The students stated that while experimenting in face-to-face education, they discussed their ideas with their friends and carried out the experiments with their friends.…”
Section: Discussionmentioning
confidence: 99%